Comfortably Numb: An Ideological Analysis of Coziness in Videogames - Andiloro, Andrea (Replay. The Polish Journal of Game Studies, 2024)
This essay analyses the concept of coziness in videogames, focusing on their role as a stress-relieving diversion in modern capitalist societies. The article emphasizes the genre’s features of safety, abundance, and softness, which create an atmosphere that soothes players amidst high-paced, contemporary lifestyles. While often framed as a type of resistant design, it is argued that cozy games uphold capitalist principles, by encouraging players to replicate them within the game. The discussion extends to the idea of coziness in interior design within these games, which is shown to reproduce ideologies of class, status, and consumerism. Drawing from atmosphere theory as well as the works of Jean Baudrillard, Slavoj Žižek, and Richard Dyer, the author argues that even the act of designing cozy spaces in these games serves as a continuation of capitalism and that cozy games may be thought of as utopian entertainment attempting to answer societal shortcomings through capitalist solutions. Thus, the essay posits that while cozy games offer a respite, they reproduce the conditions sustaining capitalist modernity.